Benin Traditional vs. The Holy Aruosa Religions: A Comparative Analysis - Bienose-Osagiede, Belinda Uhunoma; Ubuane, Gabriel O.; Udemba, Chioma Maureen (NIU Journal of Humanities; Vol 8 No 4 (2023): NIU Journal of Humanities, Vol. 8 No. 4, December 2023DO - 10.58709/niujhu.v8i4.1746, 2023)
This work is a critical evaluation of the traditional religion (worship of God through deities) vis-a-vis the emergent Holy Aruosa religion (direct worship of God, without intermediary) among the Benin of Nigeria. The work traces the histories of both religious approaches and argues that the Benin people were exposed to Western cultural influences and civilization which in turn necessitated a mixture of traditional religion and Christianity known as the Holy Aruosa. The literary research work is conducted among Benin people of Edo state, looking into written records and conducting oral tradition. The work examines the interaction between Holy Aruosa and Benin traditional religion. It gives insight into the traditional and religious lives of the people as a means of unification, identification, socialization, social stratification and ways of appreciating God (Osanobua) and posits that Holy Aruosa best represents this channel. It argues that the Holy Aruosa emerged as a response to new alignments in the social structure. The works indicates that the Benin elite-introducers of the new religion also achieved another purpose being able to modify one aspect of the indigenous religious system: the ritual approach to Osanobua. The research therefore concludes that the Benin traditional religion is the matrix for the Holy Aruosa institution; hence, Holy Aruosa religion is an offshoot of Benin traditional religion, noting, however, that the adherents of Benin traditional religion remain undaunted in their worship of Ogun, Olokun, the ancestors and the hero-divinities. Keywords: Holy Aruosa, Benin Traditional Religion, Deities